Spliceosomal introns as tools for genomic and evolutionary analysis - Irimia, Manuel (Oxford University Press, 2008)
Over the past 5 years, the availability of dozens of whole genomic sequences from a wide variety of eukaryotic lineages has revealed a very large amount of information about the dynamics of intron loss and gain through eukaryotic history, as well as the evolution of intron sequences. Implicit in these advances is a great deal of information about the structure and evolution of surrounding sequences. Here, we review the wealth of ways in which structures of spliceosomal introns as well as their conservation and change through evolution may be harnessed for evolutionary and genomic analysis. First, we discuss uses of intron length distributions and positions in sequence assembly and annotation, and for improving alignment of homologous regions. Second, we review uses of introns in evolutionary studies, including the utility of introns as indicators of rates of sequence evolution, for inferences about molecular evolution, as signatures of orthology and paralogy, and for estimating rates of nucleotide substitution. We conclude with a discussion of phylogenetic methods utilizing intron sequences and positions.